Dye-incorporated coordination polymers for direct photocatalytic trifluoromethylation of aromatics at metabolically susceptible positions - Tiexin Zhang (Nature Portfolio, 2018)
Direct trifluoromethylation of unactivated aromatic rings at metabolically susceptible positions is highly desirable in pharmaceutical fields. Here, the authors report a new approach for direct trifluoromethylation of unactivated aromatics by incorporating thiophenes into the backbone of triphenylamine-based ligand.